Versunken im Mittelmeer?: Flüchtlingsorganisationen im Mittelmeerraum und das Europäische Asylsystem - Witkowski, Juliana; Mratschkowski, Anna; Pries, Ludger (transcript, 2016)
The federal and civic organizations concerned with refugee protection and asylum have played an important part in the Mediterranean region for decades when it comes to taking in people seeking protection. However, they have hardly been scientifically examined yet – and neither have their cooperation networks. The contributions of this volume close that gap in research and show which organizations in Greece, Italy, Malta, Spain and Cyprus are active, how they work and what they can contribute to the reception and integration of persons seeking protection.